Vanskabte Land = Volaða Land [videorecording (DVD)] - Hlynur Pálmason, 1984-; Hove, Elliott Crosset, 1988-; Ingvar Sigurðsson, 1963-; Sonne, Victoria Carmen, 1994-; Lohmann, Jacob, 1974-; Hilmar Guðjónsson, 1981-; Sandø, Waage, 1943-; Ída Mekkín Hlynsdóttir; Hausswolff, Maria von, 1985-; Dirty Beaches, 1980- (Janus contemporaries., 2023)
"The struggle between the strictures of religion and humankind's brute animal nature plays out amid the beautifully forbidding landscapes of remote Iceland in this stunning psychological epic from director Hlynur Pálmason. In the late nineteenth century, Danish priest Lucas made the perilous trek to Iceland's southeastern coast to establish a church. There, the arrogant man of God finds his resolve tested as he confronts the harsh terrain, temptations of the flesh, and the reality of being an intruder in an unforgiving land. What unfolds is a transfixing journey into the heart of colonial darkness one that's attuned to both the majesty and the terrifying power of the natural world."--Container.